The Influence of Payment Schemes and Monitoring on Budgetary Slack: An Experimental Study - Aryani Intan Endah Rahmawati (Jurnal Akuntansi dan Keuangan, 2025)
The misuse and markup of the budget is one of the most prevalent forms of corruption in Indonesia. The concept is the same as budgetary slack, which is to deliberately lower the budget target to make it easier to achieve. This study investigates the impact of different payment and monitoring schemes on budgetary slack using a 2x2 experimental design. Two independent variables are manipulated: the payment system (PBP vs. FP) and the presence of monitoring (yes or no), with 140 respondents participating. The findings of this study revealed that the average budgetary slack was greater in the PBP than in the FP payment scheme. Furthermore, budgetary slack increases under the PBP payment scheme when monitoring is present. These findings contribute to the understanding of how payment and monitoring systems interact to influence behavior and decision-making in budgeting processes. These findings also suggest that organizations should carefully consider the choice of payment schemes and monitoring systems to reduce the risk of budgetary slack, as different configurations can lead to unintended increases in slack, which may undermine organizational performance and accountability.